Long-term neuromusculoskeletal side effects and quality of life in nasopharyngeal cancer patients receiving radiochemotherapy - ATASOY, BESTE MELEK; ŞANAL TOPRAK, CANAN; DANE, FAYSAL; AKYÜZ, GÜLSEREN DERYA (SPRINGER, 2020)
Aim In this study, we aimed to evaluate the neuromusculoskeletal late side effects and their impact on the quality of life of patients with nasopharyngeal carcinoma treated with radiochemotherapy. Patients and methods Twenty-seven patients were included. The mean follow-up was 61 months (range, 18-111 months). The median external radiotherapy dose applied to the nasopharynx and primary tumor was 70 Gy (range, 61-73 Gy). The mean dose received by the temporomandibular joint in the dose-volume histograms of these patients was 60.7 Gy. The maximal doses of the muscles responsible for cervical motion in different ranges were greater than 60 Gy, and the mean doses were greater than 40 Gy in the muscle groups, except for the extensor muscles. Results Two patients had brachial plexus involvement, while 89% of the patients had restriction in flexion and extension movements. Of the patients, 52% had trismus. There was a significant correlation between extension restriction and general heath score and the physical subscale of the quality-of-life questionnaire (p = 0.01). There was also a correlation between trismus and pain killer usage (p = 0.004). Conclusion This is the first study to analyze long-term muscle and nerve toxicity and their correlation between doses in nasopharyngeal cancer patients following radiochemotherapy. Despite the advances in radiotherapy techniques, it is necessary to pay attention to the doses of the nerves and muscles for late effects.
Keywords: Nasopharyngeal cancer; Radiotherapy; Brachial plexus; Late effects; Neuromusculoskeletal; PLEXUS-ASSOCIATED NEUROPATHY; RADIATION-INDUCED TRISMUS; NECK-CANCER; CONSERVATIVE SURGERY; HEAD; THERAPY; RADIOTHERAPY; CARCINOMA; COMPLICATIONS; QLQ-C30